Mathematical Relationship of Optical Density, Total Viable Count and Microbial Biomass for Growth of Serratia marcescens Strain AQ07 on Cyanide - Karamba, Kabiru Ibrahim; Ahmad, Siti Aqlima (Journal of Environmental Microbiology and Toxicology, 2019)
This study illustrates the mathematical relationship between Optical Density (OD600nm), Total Viable Cell Count (CFU/mL) and Microbial Biomass (mg/dry weight) of Serratia marcescens strain AQ07. The parameters were tested using spectrophotometric, colony-forming unit per ml and oven drying methods respectively. Bacterial density range of 0.2, 0.4, 0.6, 0.8 and 1.0 were correlated with the other two growth analyzing methods to correspond with 4.37 x 1015, 1.02 x 1016, 1.61 x 1016, 2.19 x 1016 and 2.77 x 1016 CFU/ml and bacterial biomass corresponding to 1.01, 2.14, 3.29, 4.43 and 5.57 mg/ml respectively. This illustrates a clear relationship that can be explored in the batch growth remediation process so as to avert the continuous processes of viable cell count and microbial biomass techniques at every stage in the course of research. It saves cost, time and energy exhaustion as well help in simplifying research process since there is the need for researchers to report microbial parameter in mass (mg/ml) or Colony Forming Unit/mL rather than OD600nm. Moreover; this technique can be utilized in modelling the bioremediation batch technique.